An Empirical Exploration of Volunteer Management Theory and Practice: Considerations for Sport Events in a “Post-COVID-19” World - Power, Gareth; Nedvetskaya, Olesya (Frontiers in Sports and Active Living, 2022)
The existing literature highlights some universal principles that are widely accepted as good volunteer management practice (Cuskelly, Hoye & Auld, 2006; Gallarza, Arteaga & Gil-Saura, 2013; Dunn, Chambers & Hyde, 2016). Yet, this study identified the gap that exists regarding the relationship between volunteer management theory and practice, its impact on volunteer experience, and the implications for volunteer programmes of large sporting events. Particular considerations are given to the impact of the COVID-19 Pandemic on volunteers and how it affected event organisers and volunteer managers. A mixed methods approach was adopted for this research: a survey conducted with volunteers (n=101) combined with a series of interviews with volunteers (n=8) and volunteer managers (n=6). The study identified some potential challenges facing volunteer programmes associated with large sporting events post-pandemic, particularly in relation to volunteer recruitment, pre-event volunteer management resource, and safety concerns effecting volunteer confidence to re-engage in volunteering. The challenges identified carry with them certain resource implications that event organisers need to consider in order to effectively support volunteers in re-engaging in event volunteering following the pandemic, as well as harness opportunities the pandemic has potentially created in order to successfully re-emerge from the shadow of COVID-19.